IMPACT OF FINANCIAL SERVICE ASSOCIATIONS’ CREDIT SCHEME ON INCOME OF BENEFICIARY FARMERS IN KATSINA STATE NIGERIA - SHEHU, Suleiman; Yusuf, O.; Egwuma, H. (FUDMA JOURNAL OF SCIENCES, 2022)
The study examined the impact of FSAs’ credit scheme on beneficiary farmer’s income in Katsina State, Nigeria. Primary data were collected from two categories of farmers; beneficiaries and non-beneficiaries of Financial Service Associations’ (FSAs) credit scheme with the aid of structured questionnaire and interview method. A multi-stage sampling procedure was adopted and slovin’s formula to obtained the sample size from the four Local Government Areas (LGAs): Bakori, Danja, Funtua and Malumfashi. The data were analyzed using Descriptive statistics such as percentage, frequency etc. and inferential statistics such as Propensity Score Matching (PSM) model. The results from PSM estimator revealed that FSAs’ credit scheme had a positive and statistically significant impact on the income of beneficiary farmers. The Radius matching (0.50) shows that an increase of N21, 158.360 and Kernel Matching shows an increase of N11, 977.580 on average was achieved, by beneficiary farmers who benefited from the scheme. The study revealed that there is a positive and significant impact of the loan scheme on the income of the beneficiaries in the study area at one percent level. There is a need to linking FSAs with formal financial institutions, the provision of adequate amount of loan and timely disbursement of funds to improve loan utilization by the beneficiary farmers. There is also the need to improve the administrative and management processes of the associations. The loan should be monitored by relevant bodies for effective utilization in agricultural production and other economic activities to a